Use Case of Cognitive and HCI Analysis for an E-Learning Tool (Informatica, 2014)
This paper presents the development of a new tool for an e-Learning platform, with implications and analysis from human computer interaction (HCI) and cognitonics perspectives. The goal is to improve the educational process by helping the professor form a correct mental model of each student's performance (capability). Besides this, the developed application is also analyzed from HCI and cognitive perspective with an attempt to offer an effective and highly usable tool. The interplay between cognitive psychology and HCI is emphasized as a fundamental prerequisite for a constructive and argumentative design. The main functionalities offered by the developed application are: evaluation of the level of understanding of the course material by the student and analysis of the difficulty level of the questions proposed by the professor for an exam. The prerequisites for accomplishing the task are a good structure of the on-line educational environment and information about students' activities on the platform. An important part of the process of obtaining the desired result is performing a text analysis and concept extraction on the professor's uploaded courses. The languages supported by this module are both English and Romanian. Using this module, the professor will have the ability to control the difficulty of test and exam questions and make changes accordingly: add, delete or modify test/exam questions. The developed application is thereafter discussed from HCI and cognitive psychology perspectives, such that further analysis and improvements are ready to be achieved. Our approach creates a context in which continuous design, implementation and evaluation has as output a high quality user interface suitable for an Intelligent Tutoring System.